First Nordic record of Pandava laminata (Araneae: Titanoecidae), with a synopsis of anthropochorous species of spiders in Finland - Zamani, Alireza; Koponen, Seppo (Arachnologische Gesellschaft eV, 2025)
The alien spider species Pandava laminata (Thorell, 1878) (Titanoecidae) is reported from the Nordic Region for the first time, based on a single female specimen collected in an apartment in Turku, Southwest Finland. Widely distributed in its potentially native range from East Africa through China to New Guinea and Polynesia, this species has previously been introduced to central, western and northwestern Europe through the import of ornamental plants. The specimen is illustrated with photographs, and a synopsis of obligatory synanthropic, alien, and stowaway spider species reported from Finland is provided. Additionally, previous Finnish records of introduced black widow spiders identified as Latrodectus sp. and L. mactans (Fabricius, 1775) are reattributed here to L. hesperus Chamberlin & Ivie, 1935 (Theridiidae) based on the geographical origin of the vector.